AUDIT LAYANAN TEKNOLOGI INFORMASI RUMAH SAKIT XYZ MENGGUNAKAN FRAMEWORK COBIT 5.0 (CONTROL OBJECTIVE FOR INFORMATION AND RELATED TECHNOLOGY) - Dwi Tia Shavera; Didik Kurniawan; Yunda Heningtyas (Jurnal Pepadun, 2021)
XYZ Hospital requires information technology to carry out all activities as supporting health services. Information technology service audit is needed to determine the extent of information technology services at the XYZ Hospital. This study uses the COBIT 5 framework to determine the extent of information technology capability levels at the XYZ Hospital. Data from this study were obtained based on the results of interviews, observations, and questionnaires. The results show that the capability level of the findings in the company is 2.7 which means it is at level 3 (Established). Thus, the applied process conditions already have a standard and are able to achieve the results of the processes implemented. The results of the capability level of the whole process have not reached the desired level. This difference occurs because several processes in the IT field have not been carried out maximally, there is no scheduling, review, and report on the results of problem solving.